Carbon nanotube thin film electrodes and magneto-optical spectroscopy of perovskite single crystals and thin films - Dollmann, M (2019)
With each and every passing year, weather patterns seem to become less predictable and more chaotic due to changes to worldwide climate patterns. Greenhouse gas-free energy production is a boon to the aim of preventing further rises in global temperature increases. This thesis concerns itself with one major aspect of green energy, namely photovoltaics, and some materials with great potential for application in photovoltaics, namely single-walled carbon nanotubes (SWNT), and perovskites.